STATISTICAL CONCEPTS IN BIOLOGY AND HEALTH SCIENCES - Zahir, Huma; Javaid, Aisha; Rehman, Rehana; Hussain, Zahir (Journal of Ayub Medical College Abbottabad, 2014)
In view of its applied aspects, Statistics serves as a separate mathematical science. In that respect, biostatistics is the application of statistical concepts and methods in biology, public health and medicine. One major task of medical biostatistics is to understand why a disease occurs in certain area and why that disease does not occur in other areas. In general, the advantages for properly applying statistics for a country are to keep the detailed information of people in a country. However, there must in mind be the other face of the task remembering not to adapt these surveys and limited data with entirety for quick applications that might be less advantageous. Some of the programs are much expensive and time consuming and people may feel not comfortable conveying their personal information just for the sake of applying a so called organized procedure. In such conditions, one must consider the moral values as well. Another quite unfortunate fact is that a statistical data can be misused for personal needs of a presenter. There must be ways to eradicate such customs at the governmental level. Basic and higher courses, certificate courses, diploma programs, degree programs, and other opportunities for students can be well organized and can be utilized in various employment areas in industry, government, life sciences, computer science, medicine, public health, education, teaching, research, and survey research. Statisticians, hence, are very important people for establishing various schemes, programs, institutions and organizations in medical and biological sectors. Keywords: Biostatistics, medical statistics, basic statistics and mathematical concepts, tasks and significance of biostatistics